King Faisal University’s Research Landscape: A Scientometric Analysis - Chaman Sab, M; Mueen Ahamed, KK (Information Research Communications, 2024)
This study presents a scientometric analysis of King Faisal University to evaluate its research productivity, impact, and collaboration patterns. Utilizing data spanning from 1989 to 2025, the analysis examines 10,482 research outputs, including publication trends, citation dynamics, and international partnerships. The findings reveal a steady growth in scientific output, peaking between 2017 and 2022, with an average of 13, 83 citations per document. International Collaborations constitute 73, 32% of the total publications, underscoring KFU’s global academic presence. Notable research areas include sustainability, healthcare, and advanced materials, aligning with Saudi Arabia’s Vision 2023. The study highlights KFU’s strategic contributions to multidisciplinary research and identifies both strengths and areas for targeted improvement. By employing bibliometric tools such Bibliometrix and VOSviewer, the study provides actionable insights for policymakers, researchers, and administrators to further enhance KFU’s academic and collaborative ethos.
Keywords: King Faisal University; Research landscape; Bibliomerix; OVSviewer; Web of Science